KEPERCAYAAN DAN MINAT MENGGUNAKAN KEMBALI MERUPAKAN FAKTOR DARI INDUSTRI JASA PENGIRIMAN - Mutia, Fitrahtul; Rahayu, Agus; Widjajanta, Bambang (Business Education Program of Universitas Pendidikan Indonesia, 2017)
One of business potential that growing along with the emerge of the internet usage is e-commerce. The development of e-commerce create a dynamic and competitive business competition. Delivery Services Provider become one of the biggest business opportunity that grow in this field, this service become key to determine how good an online transaction is. The trust that consumers give to the company is key to build a good buying environment. This research is propose to discover depiction of users trust on Pos Indonesia Pusat services in Bandung City, discover depiction of repurchase intention trend on users of Pos Indonesia Pusat in Bandung City and to discover the influence of trust to repurchase intention trend on users of Pos Indonesia Pusat in Bandung City. Type of research that used is verified descriptive and explanatory survey as the method with the technique of simple random sampling with sum of the sample is 130 respondent. Technique that used for the data analysis are structural equal model with the assist of a computer software of SPSS AMOS 22.0. Result of this research in general shows a significant influence of trust to repurchase intention trend. The increase the repurchase intention trend, company should make a strategy to leave a good impression on consumers and build a connection with users. Trust as the dominant influencing variabel should be controlled directly by company.Â Keywords:trust, repurchase intention, Â Article Type: Research Paper